The verbal communication of emotions : interdisciplinary perspectives - Fussell, Susan R. (L. Erlbaum Associates, 2002)
This work brings together a group of researchers focusing on the verbal communication of emotion. The chapters provide a comprehensive look at the current state of research on the use of language in affective communication.